Beyond variegation: The territorialisation of states, communities and developers in large-scale developments in Johannesburg, Shanghai and London. (June 2022) - Robinson, Jennifer; Wu, Fulong; Harrison, Phil; Wang, Zheng; Todes, Alison; Dittgen, Romain; Attuyer, Katia
Large-scale urban development projects are a significant format of urban expansion and renewal across the globe. As generators of governance innovation and indicators of the future city in each urban context, large-scale development projects have been interpreted within frameworks of 'variegations' of wider circulating processes, such as neoliberalisation or financialisation. However, such projects often entail significant state support and investment, are strongly linked to a wide variety of transnational investors and developers and are frequently highly contested in their local environments. Thus, each project comes to fruition in a distinctive regulatory context, often as an exception to the norm, and each emerges through complex interactions over a long period of time amongst an array of actors. We therefore seek to broaden the discussion from an analytical focus on variegated globalised processes to consider three large-scale urban development projects (in Shanghai, Johannesburg and London) as distinctive (transcalar) territorialisations. Using an innovative comparative approach, we outline the grounds for a systematic analytical conversation across mega-urban development projects in very different contexts. Initially, comparability rests on the shared features of large-scale developments – that they are multi-jurisdictional, involve long time scales and bring significant financing challenges. Comparing three development projects, we are able to interrogate, rather than take for granted, how a range of wider processes, circulating practices, transcalar actors and territorial regulatory formations composed specific urban outcomes in each case. Thinking across these diverse cases provides grounds for rebuilding understandings of urban development politics.